Un protocolo ubetense de 1459 y otros documentos procesales de los siglos XV y XVI - Porras Arboledas, Pedro Andrés (Cuadernos de Historia del Derecho, 2007)
Several documents coming from the municipal archives of Úbeda (Jaén) and Toledo take shelter in this work. Spanning the last Middle Age and the beginnings of the Modern Age, it also includes the oldest fragment of protocol conserved in Úbeda. Its contents are distributed between the notarial documentation and the judicial one. The present work takes account of a criminal case that ended with the victim’s probation, that included a demand for the legal portion from the aggressor’s heirs. Finally, four Toledanos documents are included: two barrister reports, a revision of executed criminal sentences and a recommendation letter in praise of a player escaped from justice.